ANIMAL TRACTION RESEARCH NETWORK BULLETIN - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The first of this bulletin publishes news of research, development, and training activities in Africa as well as brief outlines of current research. It aims to be a vehicle for exchange of information and experience for agents of national,...